Stress fracture risk factors in female football players and their clinical implications. (21st June 2007) - Warden, Stuart J; Creaby, Mark W; Bryant, Adam L; Crossley, Kay M
Abstract : A stress fracture represents the inability of the skeleton to withstand repetitive bouts of mechanical loading, which results in structural fatigue, and resultant signs and symptoms of localised pain and tenderness. Reports of stress fractures in female football players are not prevalent; however, they are probably under-reported and their importance lies in the morbidity that they cause in terms of time lost from participation. By considering risk factors for stress fractures in female football players it may be possible to reduce the impact of these troublesome injuries. Risk factors for stress fractures in female football players include intrinsic risk factors such as gender, endocrine, nutritional, physical fitness and neuromusculoskeletal factors, as well as extrinsic risk factors such as training programme, equipment and environmental factors. This paper discusses these risk factors and their implications in terms of developing prevention and management strategies for stress fractures in female football players.